Application of quantitative EEG in acute ischemic stroke patients who underwent thrombectomy: A comparison with CT perfusion. (September 2022) - Zhang, Na; Chen, Fangmei; Xie, Xufang; Xie, Zunchun; Hong, Daojun; Li, Jun; Ouyang, Taohui
Highlights: We analyzed the prognostic effects of different EEG indicators at different times on stroke patients. Quantitative EEG (QEEG) can be used as a reference for the clinical outcome of patients who underwent mechanical thrombectomy. QEEG was more powerful than CT perfusion in predicting clinical outcome at three months. Abstract: Objective: This study aimed to evaluate the predictive value of quantitative electroencephalography (QEEG) in the outcome of patients with acute ischemic stroke (AIS) who underwent mechanical thrombectomy (MT) and to assess the correlation between clinical outcome and QEEG and CT perfusion (CTP) data. Methods: Twenty-nine MT patients were included in this prospective study. Continuous electroencephalography (EEG) monitoring was performed, in which delta power, the δ/α ratio (DAR), and the (θ + δ)/(α + β) ratio (DTABR) were calculated. The clinical scores at different points were recorded. Based on the modified Ranking scale, the patients were divided into good and poor outcome groups. Several CTP parameters were recorded before MT. The correlation between QEEG, CTP parameters, and clinical scores was analyzed using the Spearman correlation analysis. The predictive value of QEEG indices and CTP parameters for the 3-month outcome was compared using the receiver operating characteristic (ROC) curve. Results: Delta power except for 7 days after MT, DAR, DATBR, and several CTP parameters were all significantly associated with the clinical scores. Although some CTP parameters were associated with the clinical scores, they were less powerful than QEEG in predicting a good or poor outcome at 3 months. Among the different explored EEG indicators, the predictive value of delta 24 h after MT was the highest. Conclusions: QEEG indices may have a certain predictive value for the outcome of AIS patients who underwent MT. Significance: QEEG may become a new prognostic tool in AIS patients who underwent MT, facilitating the planning and management of related rehabilitation plans.